Neighborhood collective efficacy and children and adolescents’ externalizing behaviors across development: A systematic review - Jiye Lee; Yui Matsuda; Daniel S. Messinger; Thomas M. O’Shea; Yue Pan; Hudson P. Santos Jr (PLoS ONE, 2026)
Objective To synthesize and describe the relationship between neighborhood collective efficacy (NCE) and children and adolescents’ externalizing behaviors to inform practice and policy decisions. Study design Data sources including PubMed, PsycINFO, and CINAHL were searched in November 2024 using the PRISMA guidelines. Literature that addressed the main predictor (neighborhood collective efficacy) and outcome (child externalizing behaviors) were included. Two authors independently evaluated the studies using the guidelines from the National Heart, Lung, and Blood Institute (NHBLI) Quality Assessment Tool for Observational Cohort and Cross-sectional studies. We developed an extraction table to categorize and analyze each study. Results We screened 294 abstracts and included 17 studies with a total of 28,957 caregiver-child (or children) dyads and 592 adolescents in November 2024 via database searches through PubMed, PsycINFO, and CINAHL. Consistent with previous literature highlighting the importance of neighborhood environment on child behavioral health outcomes, most studies demonstrated significant relationship between neighborhood collective efficacy and child externalizing behaviors across diverse developmental periods. Furthermore, studies focusing on early childhood yielded the most consistent evidence for the relationship between neighborhood collective efficacy and externalizing behaviors as compared to studies of older developmental periods. In addition, studies resulting from US-based participants were more likely to be significant than studies in other contexts. We also found limited evidence for mediating effects of corporal punishment, parenting, and adverse childhood experiences between neighborhood collective efficacy and child externalizing behaviors. Conclusions There is a significant inverse relationship between neighborhood collective efficacy and child externalizing behaviors across diverse developmental stages, populations, and study approaches.